The European administrative space over time: Mapping the formal independence of EU agencies - Eva Ruffing; Martin Weinrich; Berthold Rittberger; Arndt Wonka (Regulation & Governance, 2023)
Throughout the past decades, the EU's agency landscape has continuously expanded in size and scope. In this article, we address the lack of longitudinal data on EU agencies' formal independence. We introduce a newly revised index to measure the formal independence of EU agencies from other EU institutions over time. Applying a rules-as-data approach we coded 206 regulations and amendments to develop a new dataset covering the formal independence of all 39 EU agencies from 1975 to 2022. This longitudinal overview provides first insights about the development of formal independence at the case and population levels. At the case level we identify frequent, albeit gradual reforms of EU agencies' independence. At the population level, we observe remarkable stability in overall independence, but find stark variation across different independence dimensions. Overall, EU-level principals have shifted over time from controlling individual decisions to controlling the agencies' general decision-making apparatus.
Keywords: 330; EU administration; EU agencies; formal independence; principal agent theory; rules as data